Comparison Study Demosaicking of Bayer Color Filter Array - Naman, D. T. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Image capturing in most still and motion digital cameras employs a charge coupled device covered with a monolithic array of color filters such that each pixel samples only one color band. Interpolation is necessary to restore the missing color samples in the resulting mosaic, this process referred to as demosaicking. This paper gives an overview of demosaicking, presents few methods proposed in the literature, and concludes with a quantitative comparison of these methods for a set of images.